Analisis Struktur Teks Deskripsi Siswa Kelas VII MTS AL-IKHSAN Kabupaten Pasaman Barat - Zuraida Khairani; Najmi Hayati; Nur Wasliah (JURNAL ARMADA PENDIDIKAN, 2023)
Seventh grade MTS Al-Ikhsan students study descriptive text. However, students who struggle to write descriptive texts that fit their structure can hinder learning. In addition, students face difficulties in creating concepts and ideas in descriptive texts. As a result, the text they created did not match the existing depression text structure. This study focuses on the text structure of the descriptions. This research is a type of qualitative research that uses a descriptive approach. The source of this research data is the analysis of the text structure descriptions of students in class VII at MTS Al-IKhsan in the West Pasaman district. During the research process, we collect this data by observing and analyzing the text structure description, ensuring that the analysis is free from errors. The results of this study show that students in the 7th grade at MTS Al-Ikhsan in West Pasamana district have used the three text structures when writing descriptive text. Of the 32 descriptive texts analyzed, there are 24 complete description texts with general identifications, section descriptions, and summaries; 32 texts have section description structures, and 24 texts are summary structures.